Thermal hydraulic system of a VVER-1000 nuclear reactor and numerical simulations - Duong, Ngoc Hai (H. : ĐHQGHN, 2017)
This paper presents some results of our study on the numerical simulation of the themial hydraulic system of the Russian VVER-1000 pressurized water nuclear reactors.